Supplemental Nutrition Assistance Program (SNAP) Shoppers Experience in A Grocery Store Fruit and Vegetable Incentive Program: A Qualitative Study. Issue 4 (4th July 2022) - Ruder, Elizabeth; Demment, Meg; Graham, Meredith
ABSTRACT: The Cleaned.Cut.SNAP fruit and vegetable (FV) incentive program provided two weekly discounts of 5 off a 10 FV purchase via a grocery store loyalty card. The purpose of this study was to understand barriers to healthy eating, motivation for incentive use, redemption challenges, and perceived benefits of incentive use among participants. Twenty-two program participants in the 16-week pilot completed 1:1 semi-structured telephone interviews. The incentives helped participants overcome the barrier of affordability w to healthy eating, with cost-savings and improved health being motivators for incentive use. Participants reported purchasing/consuming more FV, improved health, food budgeting, and dietary variety during Cleaned.Cut.SNAP.